PERAN PERANGKAT DESA DALAM AKUNTABILITAS PENGELOLAAN DANA DESA (Studi pada Desa Pudaria Jaya Kecamatan Moramo) - Akib, Mulyati; Nurnaluri, Sitti; Sutrawati, Kadek (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
This study aims to determine the role of the village on the Pudaria jaya village South ofÂ Moramo fund management accountability is adequate. Data collection techniques used in this research is using interviews, documentation, and questionnaire. The sample in this study amounted to 19 people involved in fund management accountability village. This research used quantitative descriptive analysis.Results of research conducted suggests that the role of the village in a village fund management accountability can be said to have a role can be seen in the village fund management accountability. Accountability village fund management starting from the planning stage, the village did consultative meeting to discuss the Medium Term Development Plan for the Village. In the implementation of village funds grant funding submission village accompanied by RAB and the village treasurer to make payments in accordance with the RAB which has been approved by the village secretary. In the administration of cash receipts and payments made by the village treasurer done using bookkeeping inserted into a common cash book, ledger taxes and bank books. Reporting on the village fund of funds used from phase I, II, and III. In the village of accountability accountable Realization Report Implementation Budget village.Â Keywords: Role of the Village, the Village Fund Accountability